2019
DOI: 10.1002/qj.3601
|View full text |Cite
|
Sign up to set email alerts
|

Extreme rainfall sensitivity in convective‐scale ensemble modelling over Singapore

Abstract: A convective‐scale ensemble system was developed to predict the occurrence of heavy convective rainfall around Singapore with a focus on the prediction of high‐impact events. The new ensemble SINGV‐EPS has been nested within two global ensembles, MOGREPS‐G (UK Met Office) and EC‐ENS (ECMWF). Predicting the occurrence of convective rainfall in an area such as Singapore is challenging and this article discusses the use of the convection‐permitting ensemble to characterize the uncertainties in the prediction of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…However, as described in Porson et al . (2019), the same model configuration is used when running CP ensemble forecasts for Singapore. These forecasts are run at 4.5 km resolution.…”
Section: Impact Of Mass Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as described in Porson et al . (2019), the same model configuration is used when running CP ensemble forecasts for Singapore. These forecasts are run at 4.5 km resolution.…”
Section: Impact Of Mass Conservationmentioning
confidence: 99%
“…Subsequently these changes were found to improve forecasts in other parts of the Tropics as well, and so SINGV formed the starting point of the tropical science configuration in the UM science partnership (Bush et al ., 2020). The SINGV downscaler is the basis for the SINGV data assimilation system (SINGV‐DA: Heng et al ., 2020) and the SINGV ensemble prediction system (SINGV‐EPS: Porson et al ., 2019). Furthermore, SINGV is also used for sub‐kilometre urban‐scale modelling (Simón‐Moral et al ., 2020), regional climate modelling (Timbal et al ., 2019) and coupled atmosphere–ocean modelling (Thompson et al ., 2019), at CCRS.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, observed cases during YMC have been targeted for numerical modeling. In a study focusing on heavy rainfall events observed in October 2017, Porson et al (2019) examined predictions of convective rainfall over Singapore using convection-permitting regional model ensembles nested within two global ensembles. They found no clear difference of using one global ensemble versus the other, but their combination yields better results.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…The ensemble prediction system (EPS) of SINGV (SINGV-EPS) is developed from the Met Office Global and Regional Ensemble Prediction System over UK (MOGREPS-UK, Hagelin et al 2017;Porson et al 2019). The system can be considered as an ensemble of SINGV-DS forecasts.…”
Section: Singv-epsmentioning
confidence: 99%